A transient three-dimensional model for thermo-fluid simulation of cryogenic plate-fin heat exchangers. (5th November 2020) - Haider, Patrick; Freko, Pascal; Acher, Thomas; Rehfeldt, Sebastian; Klein, Harald
Highlights: A transient, three-dimensional simulation model for plate-fin heat exchangers is presented. Correlations for Colburn and Fanning (j/f) factors are applied to three-dimensional simulation model. Influence of distributor geometry on temperature distribution is shown. Three-dimensional temperature distribution during transient process is discussed. Abstract: This work proposes a novel, three-dimensional model for transient simulation of cryogenic plate-fin heat exchangers (PFHE). This model is based on the combination of computational fluid dynamics with well-established correlations for calculating heat transfer and pressure drop occurring during fluid flow through various fin types. This reduces the complex geometry of a PFHE to a geometrically simple mesh, allowing for efficient simulation of large-scale industrial PFHE. Successful validation of the model is carried out using both data available in the literature and results calculated using commercial software. The necessity for a three-dimensional model is further demonstrated using a transient case study in which the design of inlet distributors is shown to cause unfavorable distribution of fluid flow and hence severe temperature maldistribution in the PFHE. These results show that the proposed model can be useful in both detailed engineering and lifetime investigations of flexible PFHE.